2023
DOI: 10.1128/spectrum.04655-22
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomic Sequencing Reveals Host Species as an Important Factor Shaping the Mosquito Virome

Abstract: This study revealed the huge capability of mosquitoes in harboring a rich diversity of RNA viruses, although relevant studies have characterized the intensively unparalleled diversity of RNA viruses previously. Furthermore, our findings showed discernible differences not only in viromic structure between mosquito genera and even between mosquito species within the same genus but also in the genetic diversity and abundance of Wolbachia between different mosquito populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
(55 reference statements)
1
1
0
Order By: Relevance
“…We observed that while certain taxa of viruses are shared between different mosquito genera, some viral groups are restricted to specific mosquito genera. These findings align with previous studies, indicating that the composition of viral communities present in mosquitoes varies depending on the mosquito genus [ 57 , 58 , 59 ]. This supports the hypothesis that viral composition can be host-specific, implying that different mosquito species or genera may have unique viral associations.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that while certain taxa of viruses are shared between different mosquito genera, some viral groups are restricted to specific mosquito genera. These findings align with previous studies, indicating that the composition of viral communities present in mosquitoes varies depending on the mosquito genus [ 57 , 58 , 59 ]. This supports the hypothesis that viral composition can be host-specific, implying that different mosquito species or genera may have unique viral associations.…”
Section: Discussionsupporting
confidence: 92%
“…To further investigate the concept of the "core virome" in mosquitoes [11,56,57], BMSV, BMRV, BMOV1, BMOV2, BMBV1 BMBV2 and Guangzhou sobemo-like virus were quantified in 182 individual mosquitoes as they were abundantly present in our pools. The closest relatives of these seven (novel) viruses all been previously detected in mosquitoes [11,52,54,55,57,58].…”
Section: Discussionmentioning
confidence: 94%
“…albopictus is dominated by more than one virus, in this study Ae. albopictus was dominated by one virus, Guangzhou sobemo-like virus [52][53][54][55]. The reason for this could be either methodological (differences in wetlab procedures or bio-informatics methods and used thresholds), or biological (difference in ISV carriage).…”
Section: Discussionmentioning
confidence: 99%
“…More than 35,000 individuals were collected in southern Manitoba over a three-year period (2019 to 2021) and subjected to metatranscriptomic analysis. This approach has been harnessed to catalogue the microorganisms harboured by mosquitoes from other geographical regions (Shi et al 2017;Sadeghi et al 2018;Batson et al 2021;Ortiz-Baez et al 2022;Li et al 2023); however, to our knowledge this is the first study done in Canada. A distinct advantage of RNA sequencing over 16S rRNA or shotgun metagenomics is the capability to detect RNA viruses (Wensel et al 2022).…”
Section: Discussionmentioning
confidence: 99%